2022
DOI: 10.4111/icu.20210065
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of bladder and urethral injury in Korea: A nationwide population-based study

Abstract: Purpose We aimed to analyze the characteristics and management of bladder and urethral injuries in Korea by use of the National Health Insurance Service (NHIS) database. Materials and Methods Data from the NHIS database representative of all cases of Korean bladder injury (n=4,631) and urethral injury (n=17,858) reported between 2012 and 2016 were analyzed. We used the International Classification of Diseases, 10th revision, clinical modification codes to identify the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Pelvic adhesions resulting in distortion of normal anatomy are the most common risk factors for bladder injury, making dissection of the urinary bladder more challenging (Arulkumaran et al, 1986). Another Korean study reported that bladder injuries occur during hysterectomy (22%) and cesarean section (1.5%) (Tae et al, 2022). Our study showed urinary tract injuries in a few cases of group A with urinary bladder inflation just before cesarean section.…”
Section: Discussionmentioning
confidence: 50%
“…Pelvic adhesions resulting in distortion of normal anatomy are the most common risk factors for bladder injury, making dissection of the urinary bladder more challenging (Arulkumaran et al, 1986). Another Korean study reported that bladder injuries occur during hysterectomy (22%) and cesarean section (1.5%) (Tae et al, 2022). Our study showed urinary tract injuries in a few cases of group A with urinary bladder inflation just before cesarean section.…”
Section: Discussionmentioning
confidence: 50%
“…Since urethral wounds are infrequent, their occurrence has already been growing due to an increase in the number of highway vehicle accidents [ 50 ]. The preponderance of urethral injuries can be caused by either blunt trauma to the abdominal (typically coupled with a pelvic fracture) or straddling damage to the pelvis [ 38 ]. Urethral injuries caused by a pelvic fracture are frequently accompanied by numerous internal injuries (bladder, spleen, liver, and colon) and a higher risk of death [ 37 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few epidemiological studies on renal trauma in Asia, including Korea. 9 In addition, there are few studies that provide epidemiological data on treatment modalities for renal trauma; however, most of these studies have been limited to small case series. Therefore, we present epidemiological data on renal trauma using the National Health Insurance Service (NHIS) database.…”
Section: Introductionmentioning
confidence: 99%